Severe childhood trauma and clinical and neurocognitive features in schizotypal personality disorder. (23rd April 2019) - Velikonja, T.; Velthorst, E.; McClure, M. M.; Rutter, S.; Calabrese, W. R.; Rosell, D.; Koenigsberg, H. W.; Goodman, M.; New, A. S.; Hazlett, E. A.; Perez‐Rodriguez, M. M.
Abstract : Objective: Literature suggests that childhood trauma increases vulnerability for schizophrenia‐spectrum disorders, including schizotypal personality disorder (SPD). Yet, it remains unexplored whether childhood trauma predicts symptom load and the level of neurocognitive functioning in SPD. Method: We included 225 individuals with SPD and 127 healthy controls. Childhood trauma was evaluated using the Childhood Trauma Questionnaire, and schizotypal traits were assessed using the Schizotypal Personality Questionnaire. Standard neurocognitive assessments covered six cognitive domains. Results: All types of reported childhood trauma were significantly associated with SPD, in a linear fashion. Severe sexual abuse showed the greatest magnitude of association with higher cognitive–perceptual load (e.g., ideas of reference, odd belief or magical thinking); severe emotional neglect was associated with interpersonal scores (e.g., excessive social anxiety, constricted affect) within the SPD group. SPD individuals who reported severe trauma showed worse cognitive functioning (i.e., working memory, verbal/visual learning and memory, as well as verbal fluency). Conclusions: Particular severe childhood trauma types were associated with higher cognitive–perceptual and interpersonal symptoms in SPD, along with worse cognitive functioning. These findings highlight the need for clinicians to enquire about childhood trauma in SPD patients, since unaddressed early adverse experiences may carry long‐term negative consequences.